2010
DOI: 10.1021/nn100561e
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Uptake, Cytotoxicity, and Innate Immune Response of Silica−Titania Hollow Nanoparticles Based on Size and Surface Functionality

Abstract: Silica-titania hollow nanoparticles (HNPs) with uniform diameters of 25, 50, 75, 100, and 125 nm were fabricated by dissolution and redeposition method in order to evaluate size dependent cellular response. Surface-modified HNPs with cationic, anionic, and neutral functional group were prepared by silane treatment. We systematically investigated cellular internalization, toxicity, and innate immune response of HNPs in human breast cancer (SK-BR-3) and mouse alveolar macrophage (J774A.1) cells. Size- and surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
162
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 233 publications
(169 citation statements)
references
References 41 publications
6
162
1
Order By: Relevance
“…32 Induction of proinflammatory cytokines, such as IL-1, IL-6, and tumor necrosis factor, is also thought to be associated with cytotoxicity. 33 However, in the present study, no expression of IL-1 and IL-6 was found following inoculation of primary cells with naked plasmids (pIREGFP and pIREGFP-H5) or with AgNPs, AgNP-pIREGFP, or Lipo-pIREGFP.…”
contrasting
confidence: 75%
“…32 Induction of proinflammatory cytokines, such as IL-1, IL-6, and tumor necrosis factor, is also thought to be associated with cytotoxicity. 33 However, in the present study, no expression of IL-1 and IL-6 was found following inoculation of primary cells with naked plasmids (pIREGFP and pIREGFP-H5) or with AgNPs, AgNP-pIREGFP, or Lipo-pIREGFP.…”
contrasting
confidence: 75%
“…Charged NPs, eg, gold particles, are more cytotoxic than neutral forms, 29 and positively charged ZnO, silica, silica-titania hollow, and gold nanoparticles act more cytotoxically than negative variants of similar size in nonphagocytic cells. [30][31][32][33][34] Cytotoxic action of poly(amidoamine) (PAMAM) dendrimers is correlated with the number of primary amino groups, 35 and cytotoxicity of PAMAM dendrimers decreased when amine groups were neutralized with acetyl groups. 36 Also, in in vivo experiments, high numbers of primary amine groups increased the toxicity of dendrimers.…”
Section: Charge-dependent Cytotoxicitymentioning
confidence: 99%
“…Of these characteristics, the particle size is a crucial factor which determines NP endocytosis pathway [17,18], uptake rate and efficiency [6,16,[19][20][21][22], in vitro cytotoxicity [23][24][25][26][27][28], immune responses [27][28][29][30], and the final localisation [15,31,32]. Thus size-dependent uptake of various NPs has been intensively investigated and widely reported.…”
Section: Introductionmentioning
confidence: 99%
“…This could be caused by several vague parameters without clear and consistent definition. The first one is NP size, which is normally characterised as the Z-average hydrodynamic diameter (measured by light scattering technology) [29,41,50] or the number average size (measured and statistically calculated from TEM or SEM images) [6,28]. The second term is the dose of nanoparticle.…”
Section: Introductionmentioning
confidence: 99%